Gestão de custos em operadoras de plano de saúde: estudo de caso - Martins, Ana Virgínia Feitosa (2009)
The public health service in Brazil provides a poor and not effective service for the people, which in many cases, opting for private health plans. The sector is regulated by the National Agency of Health imposing rigid rules for the operation of operators, increasing the demands on the number of procedures required by the plans, but the adjustments of monthly, when released, did not accompany the growth in costs. In order to investigate strategies that could contribute to cost reduction in operating health plans, maintaining or even improving the quality of services within a qualitative methodology of study of single cases, the data collection instrument and semi -structured, in addition to the literature and documents. The analysis of indicators of the study showed that the main strategies for reducing the costs of operators are using the tertiary preventive medicine, called Home care and the coparcenary users with value added to the tuition when using examinations and consultations. It can be concluded that the analysis of strategies applied to operators of health plans, with positive results.